Risk factors for overuse running injuries - van Mechelen, W.; Hespanol Junior, L. C.; Verhagen, E. A. L. M. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Running is popular, but there is a risk of injury. Prospective studies estimate the incidence of running injuries at 10-30 RRI/1000 hours of running exposure1, 2, with at least one injury/year reported by 50% of runners3, 4. These injuries can take months to recover5. About 30% of recovered runners have recurrent injury2, 5. To decrease the burden of running injuries, it is necessary to investigate risk factors to develop preventive interventions. So far, the scientific evidence has not been very successful, because of the nature (overuse) and the multifactorial characteristic of running injuries. Also, their interactions are a complicated puzzle to solve. In addition, there is variation between studies (i.e. injury definition, follow-up period, runner characteristics & study design), making it difficult to pool data6-8. Several risk factors models have been proposed in the literature. However, only previous injuries has been consistently identified as a risk factor6. Although this information is important to develop risk factors models, this does not help to understand the causes of running injuries. Training errors may play an important role here. However, studies have failed to identify how training characteristics and their interactions contribute to injuries development9. Differences in training schemas make this question difficult to answer, but since running-related injuries are caused by running practice, the product of training volume (i.e. frequency, duration and distance) and intensity (e.g. speed, uphill, downhill & interval training) is likely a necessary influencing factor. How to investigate and interact with training characteristics is complicated; this should be investigated in future studies to provide better understanding on the causes of running injuries.